Anomalous phase change characteristics in Fe-Te materials - Fu, X. T. (2013)
Phase change materials have become significantly attractive due to its unique characteristics for its extensive applications. In this paper, a kind of phase change material, which consists of Fe and Te components, is developed. The crystallization temperature of the Fe-Te materials is 180 °C for Fe1.19Te and can be adjusted by the Fe/Te ratio. High-speed phase change in the Fe-Te materials has been demonstrated by nanosecond laser irradiation. Comparing to conventional phase change materials, the Fe-Te materials exhibit an anomalous optical property that has higher reflectivity at amorphous than crystalline state, which is useful for data storage design.